2020
DOI: 10.11604/pamj.2020.36.112.19007
|View full text |Cite
|
Sign up to set email alerts
|

Parental willingness to vaccinate adolescent daughters against human papilloma virus for cervical cancer prevention in western Nigeria

Abstract: Introduction cervical cancer, which is vaccine preventable, is the commonest gynaecological cancer worldwide. This study aimed to assess parental willingness to vaccinate adolescent girls against human papillomavirus (HPV) for cervical cancer prevention. Methods this was a descriptive cross-sectional study among 301 parents of adolescent girls who reside in Surulere Local Government Area in Lagos, Nigeria. A pretested, semi-structured interviewer-administered questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
6
10
0
Order By: Relevance
“…This study depicted that more than three-quarters (79.1%) of parents were willing to HPV vaccination of their daughters. This is in line with studies done in India, 79.9%, 34 Nigeria in different periods, 80.9% and 82%, 21 , 35 and Ethiopia; Gondar town 81.3%, 3 and Bench-Sheko zone, 79.5%. 20 This may be due to the similarity in some of the socio-demographic characteristics, such as the marital and educational status of participants.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study depicted that more than three-quarters (79.1%) of parents were willing to HPV vaccination of their daughters. This is in line with studies done in India, 79.9%, 34 Nigeria in different periods, 80.9% and 82%, 21 , 35 and Ethiopia; Gondar town 81.3%, 3 and Bench-Sheko zone, 79.5%. 20 This may be due to the similarity in some of the socio-demographic characteristics, such as the marital and educational status of participants.…”
Section: Discussionsupporting
confidence: 92%
“… 20 This may be due to the similarity in some of the socio-demographic characteristics, such as the marital and educational status of participants. From studies done in India and Nigeria, the majority (91.5%, 34 and 84.4% 21 of the study participants were married, respectively, and around 50% had accomplished college and above to their educational level, 21 which is almost similar to this study’s finding. This can be explained by being in a relationship and level of education significantly increases the acceptance and vaccination of HPV vaccine.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study and various others have shown that having higher levels of education in general and knowledge about HPV/CC increase willingness to receive vaccination. However, it has also been shown that vaccination rates in low-resource settings remain low despite willingness to vaccinate due to high cost and limited access to healthcare providers ( 34 36 ). In Pakistan, many young adult respondents believed the vaccine to be costly and time-consuming ( 37 ).…”
Section: Discussionmentioning
confidence: 99%